The Effects of Housing on Health and Health Risks in an Aging Population: A Qualitative Study in Rural Thailand. (2nd July 2014) - Somrongthong, Ratana; Dullyaperadis, Saovalux; Wulff, Anne Louise; Ward, Paul R.
Abstract : Background . Over the last decade, Thailand has experienced an aging population, especially in rural areas. Research finds a strong, positive relationship between good quality housing and health, and this paper assesses the impact and living experience of housing of older people in rural Thailand. Methods . This was a mixed-method study, using data from observations of the physical adequacy of housing, semistructured interviews with key informants, and archival information from health records for 13 households in rural Thailand. Results . There were four main themes, each of which led to health risks for the older people: "lighting and unsafe wires, " "house design and composition, " "maintenance of the house, " and "health care equipment." The housing was not appropriately designed to accommodate health care equipment or to fully support individual daily activities of older people. Numerous accidents occurred as a direct result of inadequate housing and the majority of houses had insufficient and unsafe lighting, floor surfaces and furniture that created health risks, and toilets or beds that were at an unsuitable height for older people. Conclusion . This paper provides an improved and an important understanding of the housing situation among older people living in rural areas in Thailand.